1)
[tex](x - 1)(x + 3) = {x}^{2} + 3x - x - 3 = \\ = {x}^{2} + 2x - 3[/tex]
2)
[tex]3(x - 3)(x + 1) = (3x - 9)(x + 1) = \\ = 3 {x}^{2} + 3x - 9x - 9 = 3 {x}^{2} - 6x - 9[/tex]
3)
[tex]2(x - 1)(x + 3) = (2x - 2)(x + 3) = \\ 2 {x}^{2} + 6x - 2x + 6 = 2 {x}^{2} + 4x + 6[/tex]
4)
[tex](x - 3)(x + 1) = {x}^{2} + x - 3x - 3 = \\ = {x}^{2} - 2x - 3[/tex]
Ответ: 2)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1)
[tex](x - 1)(x + 3) = {x}^{2} + 3x - x - 3 = \\ = {x}^{2} + 2x - 3[/tex]
2)
[tex]3(x - 3)(x + 1) = (3x - 9)(x + 1) = \\ = 3 {x}^{2} + 3x - 9x - 9 = 3 {x}^{2} - 6x - 9[/tex]
3)
[tex]2(x - 1)(x + 3) = (2x - 2)(x + 3) = \\ 2 {x}^{2} + 6x - 2x + 6 = 2 {x}^{2} + 4x + 6[/tex]
4)
[tex](x - 3)(x + 1) = {x}^{2} + x - 3x - 3 = \\ = {x}^{2} - 2x - 3[/tex]
Ответ: 2)